2018
DOI: 10.1038/s41467-018-07476-4
|View full text |Cite
|
Sign up to set email alerts
|

Human milk oligosaccharides, milk microbiome and infant gut microbiome modulate neonatal rotavirus infection

Abstract: Neonatal rotavirus infections are predominantly asymptomatic. While an association with gastrointestinal symptoms has been described in some settings, factors influencing differences in clinical presentation are not well understood. Using multidisciplinary approaches, we show that a complex interplay between human milk oligosaccharides (HMOs), milk microbiome, and infant gut microbiome impacts neonatal rotavirus infections. Validating in vitro studies where HMOs are not decoy receptors for neonatal strain G10P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 75 publications
(96 reference statements)
10
114
0
6
Order By: Relevance
“…Excessive Klebsiella and Escherichia-Shigella, and low abundance of Streptococcus, Veillonella, and Faecalibacterium, indicated that the small intestinal microbiota of our donors was in an unhealthy state. It has been reported that the relative abundance of Enterobacter or Klebsiella is significantly higher in breast milk of mothers of infants infected with rotavirus as well as in the intestine of the infected neonates, whereas the abundance of Streptococcus and Staphylococcus was significantly lower [24]. Our data identify a correlation between the presence of Klebsiella/Enterobacter and neonatal gastrointestinal disease, as well as a potential protective effect of Staphylococcus or Streptococcus.…”
Section: Discussionsupporting
confidence: 59%
“…Excessive Klebsiella and Escherichia-Shigella, and low abundance of Streptococcus, Veillonella, and Faecalibacterium, indicated that the small intestinal microbiota of our donors was in an unhealthy state. It has been reported that the relative abundance of Enterobacter or Klebsiella is significantly higher in breast milk of mothers of infants infected with rotavirus as well as in the intestine of the infected neonates, whereas the abundance of Streptococcus and Staphylococcus was significantly lower [24]. Our data identify a correlation between the presence of Klebsiella/Enterobacter and neonatal gastrointestinal disease, as well as a potential protective effect of Staphylococcus or Streptococcus.…”
Section: Discussionsupporting
confidence: 59%
“…Excessive Klebsiella and Escherichia-Shigella, and low abundance of Streptococcus, Veillonella, and Faecalibacterium, indicated that the small intestinal microbiota of our donors was in an unhealthy state. It has been reported that the relative abundance of Enterobacter or Klebsiella is significantly higher in breast milk of mothers of infants infected with rotavirus as well as in the intestine of the infected neonates, whereas the abundance of Streptococcus and Staphylococcus was significantly lower [24]. Our data suggests a correlation between the presence of Klebsiella/Enterobacter and neonatal gastrointestinal disease, as well as a potential protective effect of Staphylococcus or…”
Section: Discussionsupporting
confidence: 58%
“…Lately, the human milk glycans, comprising both free oligosaccharides (HMOs) and those conjugated to proteins, have started attracting research attention . It has been demonstrated that human milk glycoproteins are protective against infective diseases through antimicrobial and immunomodulatory activities .…”
Section: Other Types Of Diabetesmentioning
confidence: 99%